The Social Subcontract: Business Ethics as Democratic Theory. (June 2023) - Singer, Abraham; Ron, Amit
What does democracy demand of business? We argue that an answer to this question requires an understanding of the sorts of ethical obligations businesses have more generally. Against approaches that understand the duties of business in terms of citizenship or fiduciary obligation, we propose and develop the notion of subcontractor duties. We conceive of commercial activity as a social subcontract, in which businesses are empowered to exercise their judgment in pursuit of parochial interests, but for broader social reasons. Such license, however, puts businesses in a position to use this judgment in ways that unduly influence broader political processes. Given this, business ethics should be seen as indispensable for normative democratic theory, as it offers a conception of how business leaders should discharge their discretionary power in a manner least offensive to democratic principles. Drawing on a pragmatist understanding of democracy, we contend that businesses must respect, and avoid undermining, the formal and informal processes that characterize democratic politics. We conclude with rough sketch of what this looks like in practice, listing three broad sets of desiderata that a social subcontract seems to demand of businesses vis-à-vis democracy.